Smokeless Tobacco Cessation in an Emergency Room in Rural West Virginia - Donald Reed; Kathy Danberry (Frontiers Media S.A., 2022)
BackgroundEmergency room nurses have a strong influence on the population of smokeless tobacco users. If healthcare providers address patient's tobacco use by using a brief intervention strategy (one minute or less), it increases the quit attempt rate threefold. The object of this study is to assess the effectiveness of asynchronous internet based brief tobacco intervention training with rural emergency room nurses.MethodsA 1-h asynchronous training session on smokeless tobacco use and the 2-A and 1-R (Ask, Advise, and Refer) brief tobacco intervention strategy were given to 13 emergency room nurses at a rural acute care hospital in West Virginia. Paired sample t-tests were used to compare the pre-and post-test results.ResultsThe 1-h training session produced significant and positive increases in all items measured: increased motivation to assist patients in quitting; increased knowledge of smokeless tobacco use, its dangers, and cessation processes; increased self-efficacy in implementing brief interventions; increased perception of tobacco cessation as important; increased perception of the effectiveness of tobacco cessation interventions; and increased acknowledgment of barriers and an awareness of how to deal with them.ConclusionsThe results suggest that there is a significant potential benefit from training emergency room nurses. Brief tobacco interventions should be conducted by clinical staff during the medical history check, physical examination, or discharge phases of the emergency room visit.